Terapi Bermain Puzzle untuk Meningkatkan Konsentrasi Belajar Anak Berkebutuhan Khusus di SLB Dharma Putra Kalipucang - Parhatun Biidnillah; Ai Teti Wahyuni (Edu Happiness: Jurnal Ilmiah Perkembangan Anak Usia Dini, 2025)
The learning for autistic children requires appropriate methods that are suitable for the child's condition. Excessive behavior of autistic children results in difficulty in concentration. In order for children to concentrate on learning, it requires the right method, one of which is with games so that children feel comfortable in learning, so that children's concentration can focus on learning. Based on this, the authors are interested in conducting research on puzzle therapy at SLB Darma Putra Kalipucang Pangandaran.  The purpose of the study was to determine the puzzle play therapy to improve the learning concentration of children with special needs (autism) in SLB Dharma Putra Kalipucang. This type of research is descriptive field research. Data collection techniques through observation, interviews, and documentation. While data analysis techniques by reducing data, presenting data and verifying data. The results showed that: 1) Puzzle play therapy to improve the concentration of learning for children with special needs (autism) in SLB Dharma Putra Kalipucang has stages, namely the initial stage: room preparation, child preparation and reward preparation. Process stage: Eye Contact, Instruction, Response, Prompt, and Reward. The final stage is evaluation. 2) Supporting and inhibiting factors for the implementation of puzzle play therapy to improve the concentration of learning for children with special needs (autism) at SLB Dharma Putra Kalipucang. The encouraging factors: good communication between parents and teachers and adequate school facilities. The inhibiting factors are the presence of students with other needs that interfere with the concentration of students' learning and the food consumed, such as eating too much sugar, the child is restless.